giải giúp mình với pleaseee

Question

giải giúp mình với pleaseee

giai-giup-minh-voi-pleaseee

in progress 0
Gerda 1 year 2020-10-31T17:13:50+00:00 1 Answers 72 views 0

Answers ( )

    0
    2020-10-31T17:15:42+00:00

    Đáp án:

    3) C=-4

    Giải thích các bước giải:

    \(\begin{array}{l}
    1)A = \left( {1 – \dfrac{{\sqrt 5 \left( {\sqrt 5  + 1} \right)}}{{\sqrt 5  + 1}}} \right).\left( {\dfrac{{\sqrt 5 \left( {\sqrt 5  – 1} \right)}}{{1 – \sqrt 5 }} – 1} \right)\\
     = \left( {1 – \sqrt 5 } \right)\left( { – \dfrac{{\sqrt 5 \left( {\sqrt 5  – 1} \right)}}{{\sqrt 5  – 1}} – 1} \right)\\
     =  – \left( {1 – \sqrt 5 } \right)\left( {1 + \sqrt 5 } \right)\\
     =  – \left( {1 – 5} \right) = 4\\
    2)B = \left[ {\dfrac{{3.5\sqrt 5 }}{{15}} – \dfrac{{\left( {10 – 4\sqrt 6 } \right)\left( {\sqrt 5  + 2} \right)}}{{5 – 4}}} \right].\dfrac{1}{{\sqrt 5 }}\\
     = \left( {\sqrt 5  – \left( {10 – 4\sqrt 6 } \right)\left( {\sqrt 5  + 2} \right)} \right).\dfrac{1}{{\sqrt 5 }}\\
     = \left( {\sqrt 5  – 10\sqrt 5  – 20 + 4\sqrt {30}  + 8\sqrt 6 } \right).\dfrac{1}{{\sqrt 5 }}\\
     = \left( { – 9\sqrt 5  – 20 + 4\sqrt {30}  + 8\sqrt 6 } \right).\dfrac{1}{{\sqrt 5 }}\\
     =  – 9 – 4\sqrt 5  + 4\sqrt 6  + \dfrac{{8\sqrt 6 }}{{\sqrt 5 }}\\
    3)C = \left[ {\dfrac{{10\sqrt {10} }}{{100}} – \dfrac{{\sqrt {10} \left( {\sqrt 5  – \sqrt 2 } \right)}}{{2\left( {\sqrt 5  – \sqrt 2 } \right)}}} \right].\sqrt {10} \\
     = \left[ {\dfrac{{\sqrt {10} }}{{10}} – \dfrac{{\sqrt {10} }}{2}} \right].\sqrt {10} \\
     = 1 – 5 =  – 4\\
    4)D = \dfrac{1}{{\sqrt {25 + 2.2\sqrt 6 .5 + 24} }} – \dfrac{1}{{\sqrt {25 – 2.2\sqrt 6 .5 + 24} }} + \dfrac{1}{{\sqrt {4 – 2.2.\sqrt 3  + 3} }}\\
     = \dfrac{1}{{\sqrt {{{\left( {5 + 2\sqrt 6 } \right)}^2}} }} – \dfrac{1}{{\sqrt {{{\left( {5 – 2\sqrt 6 } \right)}^2}} }} + \dfrac{1}{{\sqrt {{{\left( {2 – \sqrt 3 } \right)}^2}} }}\\
     = \dfrac{1}{{5 + 2\sqrt 6 }} – \dfrac{1}{{5 – 2\sqrt 6 }} + \dfrac{1}{{2 – \sqrt 3 }}\\
     = \dfrac{{5 – 2\sqrt 6  – 5 – 2\sqrt 6 }}{{25 – 24}} + \dfrac{{2 + \sqrt 3 }}{{4 – 3}}\\
     =  – 4\sqrt 6  + 2 + \sqrt 3 
    \end{array}\)

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )